Current status and quantitative results of the AMYPAD prognostic and natural history study: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Alves, Isadora Lopes; Gispert, Juan Domingo; Gray, Katherine R; Collij, Lyduine; Heeman, Fiona; Salvadó, Gemma; Saint‐Aubert, Laure; Payoux, Pierre; Vellas, Bruno; Boutoleau‐Bretonnière, Claire; Gabelle, Audrey; Pasquier, Florence; et al.
Abstract: Background: Understanding the role of amyloid imaging in the earliest stages of Alzheimer's Disease (AD) becomes increasingly relevant for secondary prevention. In this context, the AMYPAD Prognostic and Natural History Study (PNHS) is an open‐label, prospective, multi‐centre cohort study (http://amypad.eu/) to determine the value of quantitative amyloid PET imaging in determining AD dementia risk. The study aims at enrolling 2000 non‐demented individuals from several European cohorts, with a focus on those with emerging amyloid pathology. Method: As of January 31 th 2020, 438 participants have consented into AMYPAD PNHS across 15 active sites. Of those, 347 are from EPAD LCS, 9 from ALFA+ and 82 from EMIF‐AD (Figure 1). To date, 329 subjects have been scanned with [ 18 F]flutemetamol or [ 18 F]florbetaben, and 108 PET scans have been analyzed with IXICO's LEAP pipeline. The primary variable is the Centiloid value (CL) using the whole cerebellum as reference region. Scans were categorized as negative (CL<12); gray‐zone (1250) for amyloid burden, and associations between CL values and age, CDR and RBANS were assessed. Result: Site activation is almost complete, with two remaining sites to be activated by February 2020. In addition to current recruitment sources, two additional cohorts (FACEHBI and FPACK) have started recruitment, and at least one more is expected in February. Current AMYPAD PNHS participants have a mean age of 67.08 ± 7.71 years and 59% of them are female. The distribution of CL values ranged from ‐12.75 to 141.79 (Figure 2), and showed a positive association with age ( p <0.001) as expected, with similar behavior for the each radiotracer (Figure 3). Forty‐five scans (42%) were classified as negative, 40 (37%) gray‐zone, and 23 (21%) positive. Within EPAD LCS participants, increasing amyloid burden was related to lower global scores on RBANS (ANOVA, F =3.6, p <0.05), and CDR=0.5 was most frequently observed in the gray‐zone (9.5%) and positive (12.0%) groups compared to amyloid‐negative subjects (2.1%). Conclusion: The AMYPAD Prognostic and Natural History Study is currently ongoing and a total of 17 sites will be actively recruiting by February 2020. Preliminary quantitative results indicate that the trial is effectively recruiting the intended target population.